Model of Contextual Learning Media in Understanding the Knowledge and Skills of Learners - Listiadi, Agung (International Journal of Scientific Research and Management (IJSRM), 2024)
AbstractThe use of teaching methods in accounting education is still rare. This can lead to students having little or no interest, lack of motivation, and learning difficulties in understanding accounting because it is unclear. The importance of this research is to understand the production process of learning media models in accounting. Develop an understanding of knowledge and skills in accounting through learning experiences based on real-world situations. The method used in this study is the use of the research model (4D) developed by Thiagarajan, with definition (interpretation), design phase, development phase and dissemination phase (distribution). The results suggest that interpretation of existing data is not sufficient to support the use of the scientific method. All students are motivated to learn the curriculum in the classroom.